Event Day 0? After‐Hours Earnings Announcements - BERKMAN, HENK; TRUONG, CAMERON (Journal of Accounting Research, 2009)
ABSTRACT In recent years, the proportion of after‐hours earnings announcements has increased to more than 40%. For after‐hours announcements, earnings‐related volume and price changes are not observed on the Compustat or I/B/E/S earnings announcement date, but one trading day later. This study demonstrates the importance of accounting for after‐hours announcements for event studies around earnings announcements.